1991
DOI: 10.1021/ef00027a015
|View full text |Cite
|
Sign up to set email alerts
|

Structural units of Athabasca asphaltene: the aromatics with a linear carbon framework

Abstract: A flash pyrolysis method has been employed, allowing the production of pyrolysis oil from Athabasca asphaltene on the multigram scale, for the identification of homologous series of n-alkylbenzenes, 9-n-alkylfluorenes, and 1-n-alkyldibenzothiophenes. These aromatic classes of compounds were concentrated from the pyrolysis oil by a sequence of selective oxidative and chromatographic steps. Identification was based on comparison of GC retention times and mass spectra with those of synthetic standards or with lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 4 publications
4
64
0
Order By: Relevance
“…[8][9][10] In the pyrolysis study, a 10% toluene solution of the n-C5-asphaltene (acetone extracted to remove coprecipitated resinous substances for 68 h) was introduced dropwise (20 drops per min) into a glass bulb kept at 430°C, and the vapors and gases evolved were swept with fast-flowing nitrogen (40 mL per min) into a cold trap. 12 At the conclusion of the pyrolysis, the trap was removed and the entire distillate subjected to column chromatographic separation on a silica-gel column. The saturates were eluted with n-pentane, the aromatics with 50% toluene/n-pentane, and the polars with 10%MeOH/toluene, yielding 0.17 g (7.0%) of polars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In the pyrolysis study, a 10% toluene solution of the n-C5-asphaltene (acetone extracted to remove coprecipitated resinous substances for 68 h) was introduced dropwise (20 drops per min) into a glass bulb kept at 430°C, and the vapors and gases evolved were swept with fast-flowing nitrogen (40 mL per min) into a cold trap. 12 At the conclusion of the pyrolysis, the trap was removed and the entire distillate subjected to column chromatographic separation on a silica-gel column. The saturates were eluted with n-pentane, the aromatics with 50% toluene/n-pentane, and the polars with 10%MeOH/toluene, yielding 0.17 g (7.0%) of polars.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, a multitude of homologous series of compounds have been isolated and identified from the saturate and aromatic fractions of the pyrolysis oil of Athabasca asphaltene. [12][13][14][15] In the present study, the polar fraction of the pyrolysis oil was separated as described in ref 12 and examined.…”
Section: Structural Details On Athabasca Asphaltenementioning
confidence: 99%
“…Asphaltenes are polynuclear aromatic species containing heteroatoms, are mildly surface active, and are known to stabilize water-in-oil emulsions [2][3][4][5]. Other natural materials present in the crude oil, such as resins, clays and surfactants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of molecular properties of asphaltenes has been carried out both with nondestructive techniques, particularly 1H and ~3C-NMR to obtain average molecular parameters [5][6][7], FT-IR to value differences in functional groups, chiefly hydroxyl, carbonyl and adjacent aromatic CH groups [12], solid-state NMR and EPR [13,14] to evaluate the degree of condensation and substitution of aromatic rings. Moreover, destructive techniques, such as pyrolysis/gas chromatography (Py/GC) [15,16] give interesting insights into the nature of aliphatic chains and of heteroatom speciation in asphaltenes. Fluorescence spectroscopy has been proved a valid tool to assess condensation of aromatic rings [17,18] especially from the differences in intensities and positions of the fluorescence bands.…”
Section: Introductionmentioning
confidence: 99%